Unlocking Buyer Intent: How the Marketing Mix Shapes Purchasing Decisions at Ummah Cahaya Restaurant - Khairani Nurbayan; Ratih Amelia; Khairatun Nazah; Muhammad Fathoni; Mega Hernawati Harefa (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study aims to examine the influence of product, price, location, and promotion on consumer purchasing decisions at RM Ummi Cahaya. Employing an associative and quantitative research design, the study involved a sample of 95 respondents selected from a population of 1,800 customers who made purchases in 2023. Data were collected through structured questionnaires and analyzed using SPSS Version 25, incorporating validity and reliability tests, multiple linear regression analysis, and hypothesis testing. The findings reveal that product, price, and location each have a positive and significant impact on purchasing decisions. However, promotion does not exhibit a significant influence. Collectively, the variables of product, price, location, and promotion demonstrate a simultaneous positive and significant effect on consumer purchasing decisions at RM Ummi Cahaya. These results suggest that enhancing product quality, competitive pricing, and strategic location may effectively increase customer purchase intentions, while promotional strategies may require further optimization to yield meaningful impact